Does Religion Matter to Equity Pricing? - El Ghoul, Sadok (Journal of business ethics, 2012)
For a sample comprising 36,105 U.S. firm-year observations from 1985 to 2008, we find that firms located in more religious counties enjoy cheaper equity financing costs. This result is robust to a battery of sensitivity tests, including alternative assumptions and model specifications, additional controls for noise in analyst forecasts, and various approaches to addressing endogeneity. In another set of tests, we find that the equity pricing role that religion plays comes predominantly from Mainline Protestants. We also document that the effect of religiosity on firms’ cost of equity capital is larger for firms (periods) lacking alternative monitoring (regulation) mechanisms as measured by lower institutional ownership (the pre-SOX era), implying that religion plays a corporate governance role. Finally, we find that the importance of religion to equity pricing is concentrated in firms that suffer lower visibility, which tend to be more sensitive to local social and economic factors. By examining the links between religiosity and valuation at the firm level, we provide strong, robust evidence supporting the perspective that religion facilitates economic development.